Wastewater Treatment of Food Industry Using Electrochemically Generated Ferrates - Kireev, Sergey; Shtepa, Vladimir N.; Kireeva, Svetlana N.; Kozyr, Alexey V.; Shikunets, Alexey B.; Naumov, Lev V.; Melzitdinov, Rodion R. (Journal of Sustainable Materials Processing and Management, 2024)
The article considers a complex technology for electrochemical wastewater treatment from a meat processing plant. The process of water treatment includes a sequential processing in graphite and iron anode-based electrochemical modules, and exposure in maturation and homogenization chamber. Ferrate generation has been evidenced in the iron anode-based module, and ferrates concurrently acting as mild oxidants, coagulants, and steel corrosion inhibitors. The electrochemical potential of ferrates ranges from 1.3 to 1.5 V in aqueous solutions for the pH values between 6 and 8. Provided an increase in ferrate concentration up to 20 mg/L in the solution, the corrosion rate for capacitive equipment and pipelines is reduced by twofold. An application of iron (III) hydroxide as a product of ferrate reduction lowers wastewater clarification by 1.5-2.0 times compared to the widely used ferric iron and aluminum salts. The research findings provide for the advancement of integrated water treatment solutions and highlight the importance of implementing efficient treatment processes to minimize the environmental impact of meat processing plants.